2014
DOI: 10.4049/jimmunol.1302795
|View full text |Cite
|
Sign up to set email alerts
|

The Specialized Proresolving Mediator 17-HDHA Enhances the Antibody-Mediated Immune Response against Influenza Virus: A New Class of Adjuvant?

Abstract: Influenza viruses remain a critical global health concern. More efficacious vaccines are needed to protect against influenza virus, yet few adjuvants are approved for routine use. Specialized proresolving mediators (SPMs) are powerful endogenous bioactive regulators of inflammation, with great clinical translational properties. Here, we investigated the ability of the SPM 17-HDHA to enhance the adaptive immune response using an OVA immunization model and a pre-clinical influenza vaccination mouse model. Our fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 59 publications
3
114
0
1
Order By: Relevance
“…Of note, MaR1 was recently identified as a potent inducer for the formation of regulatory T cells in vivo and in vitro in combination with TGFβ 70 . Only limited information is available on SPM actions on B cells, but RvD1 was recently shown to augment B cell antibody production and increase the number of antibody-producing B cells in a mouse influenza vaccination model 74 . These emerging data on the regulation of adaptive immunity by SPMs extend their range of actions and suggest a pivotal role for these imunoresolvents in the transition from innate to adaptive inflammation.…”
Section: Cellular Targets Of Spmsmentioning
confidence: 99%
“…Of note, MaR1 was recently identified as a potent inducer for the formation of regulatory T cells in vivo and in vitro in combination with TGFβ 70 . Only limited information is available on SPM actions on B cells, but RvD1 was recently shown to augment B cell antibody production and increase the number of antibody-producing B cells in a mouse influenza vaccination model 74 . These emerging data on the regulation of adaptive immunity by SPMs extend their range of actions and suggest a pivotal role for these imunoresolvents in the transition from innate to adaptive inflammation.…”
Section: Cellular Targets Of Spmsmentioning
confidence: 99%
“…Indeed, there is evidence in the literature to show that dietary n-3 PUFA supplementation can increase levels of pro-resolving lipid mediators, although there are some labs that question this possibility [34-36]. Furthermore, Phipps and co-workers have demonstrated that 17-HDHA, a hydroxylated DHA molecule, enhances the production of antibody secreting cells in vitro and in vivo [37, 38]. Therefore, we speculate that metabolo-lipidomics analyses will shed light on how n-3 PUFAs as dietary supplements may be influencing the concentrations of differing specialized pro-resolving lipid mediators and thereby the frequency of B cell subsets.…”
Section: Discussionmentioning
confidence: 99%
“…MDCK X31-HA cells were used because the NAbs tested did not have reactivity against group 2 X31 HA. Twenty-four hours post-infection, cells were washed with 1X PBS and analyzed for viral infection using a fluorescence plate reader (DTX-880, Beckman Coulter) as previously described [22, 38, 39]. Percent neutralization was determined as previously described [29].…”
Section: Methodsmentioning
confidence: 99%
“…To determine virus quantities, MDCK-HA cells were co-infected with five, two-fold serial dilutions (starting inoculum of 2,000 FFU/well) of mRFP and GFP viruses in triplicate, testing all combinations (data not shown), and the conditions that provided the highest signal above background fluorescence at 24 hours post-infection for both viruses was used. BiFMA assays were performed as described above and previously [22, 29, 38, 39]. …”
Section: Methodsmentioning
confidence: 99%